Dampak Perputaran: Aktiva Tetap dan Piutang terhadap Return on Asset pada PT Unilever Indonesia, Tbk Periode 2007-2017 - Novita, Dina; Sutiman, Sutiman; Supatmin, Supatmin (Jurnal Manajemen & Pendidikan [JUMANDIK], 2024)
This research aims to determine the impact of Fixed Asset Turnover and Receivables Turnover on Return on Assets at PT Unilever Indonesia, Tbk for the 2007-2017 period. This type of research is quantitative descriptive. The population used is the financial report of PT Unilever Indonesia, Tbk for the 2007-2017 period. Data analysis used includes Fixed Asset Turnover, Receivables Turnover and Return on Assets, descriptive tests, classical assumption tests, hypothesis tests and multiple linear regression tests. The results of the t test (partial) showed that Fixed Asset Turnover had no significant effect on Return on Assets, while Receivables Turnover had a negative and significant effect on Return on Assets. F test results (simultaneous), Fixed Asset Turnover and Receivables Turnover have a significant effect on Return on Assets with a contribution of 30.25%. This is also reinforced by the results of the value of fcount (5.876) > ftable (4.260).